Diseños industriales y conocimientos tradicionales: estudio comparado de Legislación en América Latina. - Murillo Siquihua, Jeison Polo (2024)
The present research work refers to the comparative study of the legal regulation of the legal protection of traditional knowledge in the industrial property standards of industrial designs of several Latin American countries (Argentina, Peru, Colombia, Venezuela) and the options that offers, compared to Ecuadorian regulations. The issue has been analyzed internationally since the 1970s, based on the denunciation and search for protection measures for communities against the illicit appropriation of their traditional knowledge by outsiders. There are national experiences of this type of regulations from the point of view of positive and preventive protection, in terms of intellectual property. Currently, WIPO is evaluating draft provisions for its international protection in a comprehensive instrument that includes the possibility of protection by existing national industrial property systems such as industrial designs, or sui generis systems, depending on the national reality. Of each country. Latin America has an impressive cultural diversity with significant traditional knowledge and intellectual property legislation. The Andean Community of Nations has Decision 486, which dates back to 2000, on industrial property, so it is necessary to study the current regulations of the region taking into account that time has passed and that Ecuador has new regulations and that in the country There is no documentary evidence of a study similar to the one intended on the subject that systematizes theoretical and normative foundations in this regard. A qualitative theoretical investigation is proposed with the use of analysis-synthesis, inductive-deductive, analytical exegetic and comparative law methods, as well as the use of the bibliographic review technique. As expected results, it is expected to obtain a comparative study of legislation that analyzes the protection of traditional knowledge through industrial designs in Latin 5 America (Argentina, Peru, Colombia, Venezuela) and in particular, in the Republic of Ecuador, which systematizes its theoretical foundations. and regulations, as well as the opportunities for its practice at the national level. Keywords: industrial designs, traditional knowledge, comparative law, industrial property